Pengaruh Kualitas Produk dan Citra Merek terhadap Penjualan Frozen Food CV. Sakana Indo Prima di Bojongsari Kota Depok - Soekarsono, Rame; Hakim, Lukman Nul; Permata Sari, Mega Khadizah (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
Progress change style life public the passage of time, society own assessment each to choose something product Good from quality product nor image brand. Indonesian society in the present era, start to adapt self with a style of life practical with consuming  frozen food  as it is outside the country. Objective study This is To know how to influence Quality Products and Brand Image to Sale  Frozen food  CV. Sakana Indo Prima at Bojongsari City of Depok . Study This is a study quantitative. A sample totaling 105 respondents was taken with the technique  of simple random sampling.  Data analysis used is analysis multiple linear regression, T-test, F-test, and coefficient determination. Results study based on test T, and test F, obtained that Quality Product influential positive And significant to the sale by 61.4% and Brand Image influential positive And significant to Sales by 64.2%. And Quality Product and Brand Image influential positive And significant to sales of 69.0 %.